Did the ACA Medicaid Expansion Save Lives? - Mark Borgschulte; Jacob Vogler (Institute of Labor Economics (IZA), 2019)
We estimate the effect of the Affordable Care Act Medicaid expansion on county-level mortality in the first four years following expansion. We find a reduction in all-cause mortality in ages 20 to 64 equaling 11.36 deaths per 100,000 individuals, a 3.6 percent decrease. This estimate is largely driven by reductions in causes of death likely to be influenced by access to health care, and equates to one life saved per 310 newly covered individuals. A cost-benefit analysis shows that the improvement in welfare due to mortality responses may offset the entire net-of-transfers expenditure associated with the expansion.
Keywords: H75; I13; I14; I18; I38; 330; health insurance; Medicaid; mortality; public health insurance; healthcare; Affordable Care Act